Diagnostic Imaging of Severe Pneumonia COVID-19: A Comprehensive Systematic Review - Claudia Bella Laurentia; Tri Harjanto; Tiarma Saulina (The International Journal of Medical Science and Health Research, 2025)
Background: COVID-19, caused by SARS-CoV-2, has become a global health crisis since its emergence in December 2019. Severe pneumonia is a critical manifestation of the disease, often necessitating diagnostic imaging for effective management. This systematic review evaluates the diagnostic imaging features of severe pneumonia in COVID-19 using chest X-ray (CXR), computed tomography (CT), lung ultrasound (LUS), and magnetic resonance imaging (MRI). Methods: This review follows PRISMA 2020 guidelines. Studies from 2019–2024 were screened for peer-reviewed evaluations of imaging findings in severe COVID-19 pneumonia. Results: Eight studies were included. Key findings demonstrated the utility of LUS in detecting early abnormalities like B-lines, critical for bedside monitoring. CXR served as a prognostic tool with radiographic severity scores correlating with adverse outcomes. CT provided detailed anatomical insights, identifying ground-glass opacities (GGO), consolidations, and disease severity markers. MRI, while less commonly used, showed comparable sensitivity and specificity to CT, with advantages in radiation-free imaging for specific populations. Discussion: The reviewed studies highlight the complementary roles of imaging modalities in managing COVID-19 pneumonia. Key imaging features include ground-glass opacities, consolidations, and crazy-paving patterns, predominantly in peripheral and lower lung regions.        Conclusion: Imaging modalities play complementary roles in managing severe COVID-19 pneumonia. LUS is ideal for bedside assessments, CXR aids in prognostication, CT remains the gold standard for detailed evaluation, and MRI offers a viable alternative for radiation-sensitive cases. Understanding these modalities' applications can enhance diagnostic accuracy and clinical outcomes.